Application of the dusty plasma technology for diamond ceramics production - Pal, Alexander; Ekimov, Evgeny; Ivanov, Alexander; Borovikov, Nikolay; Rusinkevich, Andrey; Ryabinkin, Alexey; Serov, Alexander; Starostin, Andrey; Fortov, Vladimir; Gromnitskaya, Elena (International Conference on Plasma Surface Engineering, 2013)
Not available